Millimetre‐wave dielectric resonator antenna array based on directive LTCC elements. Issue 5 (5th March 2018) - Mrnka, Michal; Cupal, Miroslav; Raida, Zbynek; Pietrikova, Alena; Kocur, Dusan
Abstract : The study deals with the application of low‐temperature co‐fired ceramic (LTCC) technology for design of a higher‐order mode dielectric resonator antenna element operating at centre frequency 25.7 GHz. The LTCC material that the authors use provides very low dielectric losses and enables us to design an antenna element with very high radiation efficiency. The authors follow by examining the mutual coupling between two resonators and the authors propose a small (1 × 4) one‐dimensional antenna array composed of such elements. In order to minimise the dimensions of the ground plane and to place the connector at a convenient location, the authors design a parallel feed network in substrate integrated waveguide technology, thus reducing the radiation losses of the feeding structure. The experiments verify the four‐element antenna array concept with maximum measured gain of 16.3 dBi.